12(R)-hydroxyicosatetraenoic acid: a cytochrome-P450-dependent arachidonate metabolite that inhibits Na+,K+-ATPase in the cornea. - Schwartzman, M L (1987)
When corneal microsomes were incubated with arachidonic acid in the presence of an NADPH-generating system, four polar metabolites (compounds A-D) were formed. Synthesis of these metabolites could be inhibited by carbon monoxide, SKF 525A, and anti-cytochrome c reductase antibodies. One of the metabolites, compound C, was found to inhibit partially purified Na+,K+-ATPase from the corneal epithelium in a dose-dependent manner with an ID50 of approximately 50 nM. After compound C was purified by TLC and HPLC, it was found to have a UV absorption spectrum with a maximum absorbance at 236 nm suggesting the presence of a conjugated diene. Mass spectrometric analysis using positive- and negative-ionization modes was carried out on derivatized compound C that had been synthesized from a mixture of specifically labeled ([5,6,8,9,11,12,14,15-2H8]arachidonic acid) and unlabeled arachidonic acid. Abundant fragment ions were consistent with compound C being a monooxygenated derivative of arachidonic acid with a hydroxyl substituent at carbon-12 of the icosanoid backbone; all deuterium atoms from [2H8]arachidonate were retained in the structure. Oxidative ozonolysis yielded products indicating double bonds between carbons at positions 10 and 11 and positions 14 and 15 of the 20-carbon chain. Compound C was, therefore, characterized as a 12-hydroxyicosatetraenoic acid. However, only 12(R) isomer was found to be an inhibitor of the Na+,K+-ATPase from the corneal epithelium, suggesting that the biologically active compound C was 12(R)-hydroxy-5,8,10,14-icosatetraenoic acid. Such an inhibitor of Na+,K+-ATPase synthesized in the cornea may have an important role in regulating ocular transparency and aqueous human secretion.